Effect of silicon addition on microstructure and mechanical properties of grey cast Iron: An overview. (2020) - Singhal, Prachi; Saxena, Kuldeep K.
Abstract: Grey cast iron is used to make brake disc due to its high damping vibration resistance and low cost. In the present work, effect of silicon addition on microstructure and mechanical properties of grey cast iron is reviewed. Results of microstructure and mechanical properties are compiled, which are affected due to the addition of silicon in grey cast iron. From the review, it is found that the volume of soft graphite flakes increases i.e. grain size increases which reduces the hardness of grey cast iron, on increasing the silicon content. Similarly, tensile strength reduces as a function of silicon addition. Hardness and wear rate depends on the phase of microstructure and the size of graphite flakes. Maximum hardness was obtained at 3.33% of silicon content.